2017
DOI: 10.1007/s00266-017-0794-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acellular Dermal Matrix (ADM) Use Under Mastectomy Flap Necrosis on Perioperative Outcomes of Prosthetic Breast Reconstruction

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“… 10 , 24 Previous studies, however, have shown a high variance in complication rate with this technique, ranging from only 5% up till 50%. 4 , 7 9 It can be expected that patient-reported satisfaction rates vary analogously; however, this has not been clearly established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 24 Previous studies, however, have shown a high variance in complication rate with this technique, ranging from only 5% up till 50%. 4 , 7 9 It can be expected that patient-reported satisfaction rates vary analogously; however, this has not been clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the safety of ADM use in IBBR vary widely, with complication rates ranging from below 5% to more than 50%. 4 , 7 9 Recent results indicate that expertise with both the technique and the careful selection of eligible patients are important factors for optimal clinical outcomes. 9 , 10 However, to assess to what extent the eventual goal of breast reconstructive surgery is reached, that is, to enhance the quality of life, measurement of patient-reported outcomes (PROs) is essential.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Kim and Bang linked the use of ADM and the mastectomy flap necrosis [ 28 ]. Powell-Brett and Goh [ 113 ] reported 10.4% cases of skin necrosis in a study with ADM-assisted immediate breast reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…Immediate breast reconstruction (IBR) received an important boost in popularity as a consequence of the advent of ADMs [ 2 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The use of ADMs showed encouraging results but conflicting reports as well [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. ADMs-assisted breast reconstruction can be divided into pre-pectoral and submuscular.…”
Section: Introductionmentioning
confidence: 99%
“…fused mastectomy flaps, which ultimately leads to matrix disintegration and possible complications[17] [18] [19] [20]. Rapid integration of ADM is important to avoid complications such as seroma or infection[21]. A study by Kim et al showed that the use of ADM in case of necrotic mastectomy flap led to higher explantation rates, although only with borderline statistical significance[21].C.…”
mentioning
confidence: 99%